Katalog der in den Sammlungen der Abteilung Taxonomie der Insekten des Institutes für Pflanzenschutzforschung, Bereich Eberswalde (ehemals Deutsches Entomologisches Institut), aufbewahrten Typen - XVII (Coleoptera: Scydmaenidae, Orthoperidae, Discolomidae, Ptiliidae, Scaphiidae). - Gaedike, Hannelore (Contributions to Entomology = Beiträge zur Entomologie, 1978)
The present catalogue includes the types of Coleoptera (Scydmaeneidae, Orthoperidae, Discolomidae, Ptiliidae, Scaphiidae) preversed in the collection of the Department of Taxonomy of Insects of the Institut of Plant Protection Research, Eberswalde (former Deutsches Entomologisches Institut).